Metal nano-catalyst as well as preparation method and application thereof

The carbon dispersed metal nanocatalyst prepared by one-step method solves the problem of low efficiency in extracting hydrogen from organic solid waste in the prior art under microwave catalysis, and realizes efficient and highly selective hydrogen extraction and by-product of high-value carbon materials.

CN119524850APending Publication Date: 2025-02-28TECHNICAL INST OF PHYSICS & CHEMISTRY - CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311120115.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-31
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The prior art is difficult to extract hydrogen from organic solid waste efficiently and selectively, and conventional thermal catalytic reactions are low in efficiency, complex products, and difficult to separate and purify.

Method used

A metal nanocatalyst is prepared by a one-step method, and a carbon-dispersed metal nanocatalyst is formed by calcining the transition metal salt of carbon-containing elements, which is used to microwave catalytically decompose organic solid waste.

Benefits of technology

It achieves efficient and highly selective extraction of hydrogen from organic solid waste, with hydrogen selectivity in gas products being higher than 60%, and at the same time, high-value carbon materials such as filamentous carbon are produced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524850A_ABST
    Figure CN119524850A_ABST
Patent Text Reader

Abstract

The invention provides a metal nano-catalyst as well as a preparation method and application thereof. The preparation process of the metal nano-catalyst comprises the following steps: roasting transition metal salt at 300-1000 DEG C for 1-6 hours to obtain the metal nano-catalyst, wherein the transition metal salt at least contains one transition metal salt containing a carbon element. The preparation method is simple and convenient to operate, easy to control and low in cost, the obtained metal nano-catalyst can be used for a dehydrogenation reaction for microwave catalytic decomposition of organic solid waste, the catalytic efficiency is high, high-yield and high-purity hydrogen can be obtained, the selectivity of hydrogen in a gas product is higher than 60%, meanwhile, high-value filamentous carbon is produced as a byproduct, and the method is suitable for industrial production. The catalytic conversion from wastes to high-value products is successfully realized, and the method has a relatively high application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of energy regeneration, and specifically comprises a metal nanocatalyst and a preparation method and application thereof. Background Art

[0002] The non-renewable nature of fossil energy and the huge consumption of fossil energy by humans have led to the gradual depletion of fossil energy. At the same time, the large-scale consumption of fossil energy has caused greenhouse gas emissions, increased greenhouse gas concentrations in the atmosphere, and enhanced the greenhouse effect (CO2 is the main part of greenhouse gases, of which more than 90% of CO2 emissions are generated by fossil energy consumption activities), leading to global warming.

[0003] Hydrogen is a clean, abundant and non-toxic fuel, and is expected to be used as a substitute for carbon-based fuels to achieve energy transformation and sustainable development. Hydrogen storage materials with wide sources, rich resources, high hydrogen content and stable properties will greatly promote the development of hydrogen energy. Using organic solid waste as raw materials to produce hydrogen is an effective way to control environmental pollution and develop clean energy. For example, plastics contain 8-14wt% hydrogen, which means that plastics can be used as a hydrogen storage material with high hydrogen content and wide sources, and clean hydrogen energy can be extracted by appropriate methods. However, the current use of organic solid waste to produce hydrogen requires relatively harsh reaction conditions and chemical conversion processes, and there are also huge challenges in efficiently and selectively extracting hydrogen from organic solid waste. Conventional thermal catalytic reactions often have low dehydrogenation efficiency, and the gas products obtained are complex, resulting in reduced product value and difficulty in separation and purification. Although the improved pyrolysis-catalytic reforming method can improve the dehydrogenation efficiency and hydrogen yield, it usually requires a long reaction time at high temperature (>500℃), which consumes a lot of energy and increases carbon dioxide emissions.

[0004] Therefore, it is urgent to develop a catalyst that can achieve efficient and highly selective extraction of hydrogen from organic solid waste, which is crucial to promoting the recycling and reuse of organic solid waste, solving environmental pollution and the development of hydrogen energy. Summary of the invention

[0005] In view of the above problems existing in the prior art, the first object of the present invention is to provide a method for preparing a metal nanocatalyst. The preparation method adopts a one-step method to prepare and synthesize a metal nanocatalyst with excellent catalytic performance, and the preparation process is simple, easy to control, and low in cost.

[0006] The second object of the present invention is to provide a metal nanocatalyst prepared by the preparation method as described above.

[0007] The third object of the present invention is to provide an application of the metal nanocatalyst as described above in microwave catalytic decomposition of organic solid waste.

[0008] To achieve the above first object, the technical solution adopted by the present invention includes:

[0009] The present invention discloses a method for preparing a metal nanocatalyst, comprising the following steps:

[0010] calcining the transition metal salt at 300-1000°C for 1-6h to obtain a metal nanocatalyst;

[0011] Wherein, the transition metal salt contains at least one transition metal salt containing carbon elements.

[0012] Experiments have found that when carbon-containing transition metal salts are introduced as raw materials to prepare catalysts, carbon will spontaneously form during the preparation process, which can effectively disperse and isolate the formed metal particles, prevent them from aggregating into large particles and sintering, and improve the microwave thermal conversion efficiency, which is beneficial to the catalytic dehydrogenation of organic solid waste.

[0013] Further, the transition metal salt is selected from one or more of nickel salts, cobalt salts and iron salts;

[0014] The nickel salt includes but is not limited to one or more of nickel acetate, nickel nitrate, nickel chloride and nickel acetylacetonate;

[0015] The cobalt salt includes but is not limited to one or more of cobalt acetate, cobalt nitrate, cobalt carbonyl, cobalt chloride and cobalt acetylacetonate;

[0016] The iron salt includes, but is not limited to, one or more of ferric citrate, ferric nitrate, ferric acetylacetonate and ferric acetate.

[0017] When the transition metal salt is selected from any one of nickel salts, cobalt salts and iron salts, the obtained catalyst is a metal nanocatalyst composed of a single metal compound; when the transition metal salt is selected from any two or three types of metal salts among nickel salts, cobalt salts and iron salts, the obtained catalyst is a metal nanocatalyst composed of a multi-metal compound. It can be understood by those skilled in the art that when the raw material is a single transition metal salt, the transition metal salt can be directly roasted to obtain; when the raw material is a plurality of transition metal salts, in order to better mix the transition metal salts, a small amount of water can be added to dissolve and disperse the transition metal salts, and then the subsequent roasting operation is performed while ensuring that the transition metal salts are fully mixed, which is conducive to making the metal nanocatalyst present a higher catalytic activity. In a specific embodiment, the mass ratio of the total mass of the transition metal salt to water is 1:0.05-50; preferably 1:0.1-20.

[0018] Further, when the transition metal salt is selected from nickel salt and cobalt salt, the mass ratio of the nickel salt to the cobalt salt is 1:0.01-100; illustratively, the mass ratio of the nickel salt to the cobalt salt can be 1:0.01, 1:0.1, 1:0.5, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:20, 1:50, 1:100 and the like.

[0019] Further, when the transition metal salt is selected from nickel salt and iron salt, the mass ratio of the nickel salt to the iron salt is 1:0.01-100; illustratively, the mass ratio of the nickel salt to the iron salt can be 1:0.01, 1:0.1, 1:0.5, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:20, 1:50, 1:100 and the like.

[0020] Further, when the transition metal salt is selected from cobalt salt and iron salt, the mass ratio of the cobalt salt to the iron salt is 1:0.01-100; illustratively, the mass ratio of the cobalt salt to the iron salt can be 1:0.01, 1:0.1, 1:0.5, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:20, 1:50, 1:100 and the like.

[0021] Furthermore, when the transition metal salt is selected from nickel salt, cobalt salt and iron salt, the mass ratio of the nickel salt, cobalt salt and iron salt is 1:0.01-100:0.01-100; preferably, the mass ratio of the nickel salt, cobalt salt and iron salt is 1:0.1-10:0.5-10.

[0022] Further, when the transition metal salt includes a transition metal salt containing a carbon element and a transition metal salt not containing a carbon element, the mass ratio of the transition metal salt containing a carbon element to the transition metal salt not containing a carbon element is 0.1-20:1; illustratively, the mass ratio of the transition metal salt containing a carbon element to the transition metal salt not containing a carbon element can be 0.1:1, 0.25:1, 0.5:1, 0.625:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, 20:1 and the like.

[0023] Furthermore, the calcination atmosphere is selected from one of air atmosphere, inert atmosphere and H2 / inert gas mixed atmosphere. It should be noted that when the calcination atmosphere is air atmosphere, the process for preparing the catalyst can be regarded as a combustion process, that is, the transition metal salt is burned and decomposed in the air atmosphere, and in this process, the carbon-dispersed metal nanocatalyst can be obtained by flexibly adjusting the metal salt raw material and the calcination temperature, that is, part of the carbon element of the metal salt raw material containing carbon element will be carbonized and coated around the nanoparticles during the calcination process, and the nanoparticles are dispersed to prevent them from aggregating into large particles, thereby promoting the exposure of catalytic sites and improving catalytic activity. When the calcination atmosphere is an inert atmosphere, the process for preparing the catalyst can be regarded as a decomposition process, that is, the transition metal salt is heated and decomposed in an oxygen-free or low-oxygen atmosphere. In this process, the carbon generated by the carbonization of the carbon-containing metal salt raw material can be well retained, and the metal nanoparticles can be dispersed to avoid the loss of the generated carbon due to the combustion of carbon dioxide in the presence of oxygen; when the calcination atmosphere contains some reducing gas H2, the nano metal oxides generated by the decomposition can be further reduced to metal elements or metal alloy compounds, reducing the production of carbon oxides and improving hydrogen selectivity.

[0024] Furthermore, the inert atmosphere is selected from one or more of nitrogen, argon and helium.

[0025] To achieve the above second purpose, the technical solution adopted by the present invention includes:

[0026] The invention discloses a metal nanocatalyst, which is prepared by the preparation method as described above.

[0027] Furthermore, the particle size of the metal nanocatalyst is 1-500 nm.

[0028] To achieve the third objective, the technical solution adopted by the present invention includes:

[0029] The present invention discloses an application of the metal nanocatalyst as described above in catalytic decomposition of organic solid waste.

[0030] Further, the application is specifically:

[0031] Under an inert atmosphere, the organic solid waste and the metal nanocatalyst are placed in a microwave reactor, treated at a microwave power of 300-2000 W for 1-20 minutes, and the reaction products are collected and separated.

[0032] Furthermore, the organic solid waste includes, but is not limited to, one or more of crop straw, forestry waste, waste plastic, cellulose, hemicellulose, lignin, lignocellulose, monosaccharides, amino acids and polysaccharides.

[0033] Furthermore, the blending mass ratio of the metal nanocatalyst to the organic solid waste is 0.05-30:1; illustratively, the blending mass ratio of the metal nanocatalyst to the organic solid waste can be 0.05:1, 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 20:1, 30:1 and the like.

[0034] Beneficial effects of the present invention:

[0035] The invention provides a method for preparing a metal nanocatalyst. The method can prepare a metal nanocatalyst with excellent catalytic activity through a simple one-step process. The method is simple to operate, easy to control and low in cost.

[0036] The metal nanocatalyst obtained by the preparation method provided by the present invention has a good dispersion effect in structure and morphology. The carbon spontaneously formed during the preparation of the metal nanocatalyst can effectively disperse and isolate the formed metal particles, so that the various metal active species in the multi-metal catalyst do not aggregate and sinter, which is beneficial to the synergistic catalytic dehydrogenation of organic solid waste among the metal species.

[0037] The use of metal nanocatalysts in microwave catalytic decomposition of organic solid waste can selectively catalyze the breaking of CH bonds in the reaction substrate, so that the hydrogen in the reaction substrate can be efficiently removed, thereby obtaining high-purity and high-yield hydrogen. The selectivity of hydrogen in the obtained gas product is higher than 60%. At the same time, high-value carbon materials can be produced as by-products during the reaction process. The carbon material is filamentous carbon mainly composed of carbon nanotubes, which realizes the catalytic conversion of waste into high-value products and has high application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings.

[0039] Figure 1 The process flow chart of the catalytic reaction in the present invention is shown.

[0040] Figure 2 The XRD patterns of the catalysts prepared in Example 1, Example 2, Example 5 and Example 6 are shown.

[0041] Figure 3 SEM images and TEM images of the catalysts prepared in Example 2, Example 6, and Example 7 are shown.

[0042] Figure 4 SEM images and TEM images of carbon materials generated by the reactions of Example 1, Example 4, and Example 10 are shown. DETAILED DESCRIPTION

[0043] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and drawings. It should be clear that the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] Example 1

[0045] This embodiment provides a method for microwave catalytic dehydrogenation of polyethylene plastics, and the specific operating steps are as follows:

[0046] 1) crushing the collected polyethylene plastic and mixing it with the cobalt-iron bimetallic nanocatalyst in a mass ratio of 1:1;

[0047] The cobalt-iron bimetallic nanocatalyst used in step 1 is prepared according to the following method:

[0048] The iron nitrate and cobalt acetate were mixed in a mass ratio of 1:1.6, and then deionized water was added and stirred into a uniform gel. The total mass ratio of deionized water to the two metal salts was 1:5. The gel catalyst precursor was placed in a muffle furnace and calcined at 450° C. in an air atmosphere for 2 hours to obtain a cobalt-iron bimetallic nanocatalyst.

[0049] 2) If Figure 1 As shown, 10 g of the uniformly mixed reaction material in step 1 was taken and placed in a microwave reactor, and purged with nitrogen for 10 min (100 ml / min) to exclude oxygen before microwave irradiation, and then a catalytic dehydrogenation reaction was carried out at a microwave power of 800 W for 10 min. The reaction product was condensed and separated to obtain gas and oil, and solid residue remained in the reactor. The product composition was then quantitatively and qualitatively analyzed, and the results are shown in Table 1.

[0050] Table 1 Distribution of products from microwave catalytic dehydrogenation of polyethylene

[0051]

[0052] Example 2

[0053] This embodiment provides a method for microwave catalytic dehydrogenation of polyethylene plastics, and the specific operating steps are as follows:

[0054] 1) crushing the collected polyethylene plastic and mixing it with the nickel-cobalt bimetallic nanocatalyst in a mass ratio of 2:1;

[0055] Wherein, the nickel-cobalt bimetallic nanocatalyst used in step 1 is prepared according to the following method:

[0056] Nickel acetate and cobalt acetylacetonate were mixed in a mass ratio of 2:3, and then deionized water was added and stirred into a uniform gel, and the total mass ratio of deionized water to the two metal salts was 1:2. The gel catalyst precursor was calcined at 450°C in an air atmosphere for 3 hours to obtain a nickel-cobalt bimetallic nanocatalyst;

[0057] 2) If Figure 1 As shown, 12 g of the uniformly mixed reaction material in step 1 was taken and placed in a microwave reactor, and purged with nitrogen for 10 min (100 ml / min) to exclude oxygen before microwave irradiation, and then a catalytic dehydrogenation reaction was carried out at a microwave power of 1000 W for 10 min; the reaction product was condensed and separated to obtain gas and oil, and solid residue remained in the reactor. The product composition was then quantitatively and qualitatively analyzed, and the results are shown in Table 2.

[0058] Table 2 Distribution of products from microwave catalytic dehydrogenation of polyethylene

[0059]

[0060] Example 3

[0061] This embodiment provides a method for microwave catalytic dehydrogenation of polyethylene plastics, and the specific operating steps are as follows:

[0062] 1) crushing the collected polyethylene plastic and mixing it with the nickel-cobalt bimetallic nanocatalyst in a mass ratio of 2:1;

[0063] Wherein, the nickel-cobalt bimetallic nanocatalyst used in step 1 is prepared according to the following method:

[0064] Nickel acetate and cobalt acetylacetonate were mixed in a mass ratio of 2:3, and then deionized water was added and stirred into a uniform gel, and the total mass ratio of deionized water to the two metal salts was 1:2. The gel catalyst precursor was calcined at 450°C and 50ml / min of a 10vol% H2 / inert gas mixed atmosphere for 3h to obtain a nickel-cobalt bimetallic nanocatalyst;

[0065] 2) If Figure 1 As shown, 12 g of the uniformly mixed reaction material in step 1 was taken and placed in a microwave reactor, and purged with nitrogen for 10 min (100 ml / min) to exclude oxygen before microwave irradiation, and then a catalytic dehydrogenation reaction was carried out at a microwave power of 1000 W for 10 min; the reaction product was condensed and separated to obtain gas and oil, and solid residue remained in the reactor. The product composition was then quantitatively and qualitatively analyzed, and the results are shown in Table 3.

[0066] Table 3 Distribution of products of polyethylene microwave catalytic dehydrogenation

[0067]

[0068] Example 4

[0069] This embodiment provides a method for microwave catalytic dehydrogenation of polyethylene plastic and biomass mixture, and the specific operation steps are as follows:

[0070] 1) The collected polyethylene plastic and rice straw were crushed and mixed in a mass ratio of 9:1, and then mixed with nickel-cobalt-iron trimetallic nanocatalyst in a mass ratio of 1:2;

[0071] Wherein, the nickel-cobalt-iron trimetallic nanocatalyst used in step 1 is prepared according to the following method:

[0072] Nickel nitrate, cobalt acetate and ferric acetylacetonate were mixed in a mass ratio of 1:1:3, and then deionized water was added and stirred into a uniform gel, the total mass ratio of deionized water to trimetallic salt was 1:5, and the gel catalyst precursor was calcined at 600° C. in an air atmosphere for 3 h to obtain a nickel-cobalt-iron trimetallic nanocatalyst;

[0073] 2) If Figure 1 As shown, 30 g of the uniformly mixed reaction material in step 1 was taken and placed in a microwave reactor, and purged with nitrogen for 10 min (100 ml / min) before microwave irradiation to exclude oxygen; then a catalytic dehydrogenation reaction was carried out at a microwave power of 1200 W for 15 min, and the reaction product was condensed and separated to obtain gas and oil, and solid residue remained in the reactor. The product composition was then quantitatively and qualitatively analyzed, and the results are shown in Table 4.

[0074] Table 4 Distribution of products from microwave catalytic dehydrogenation of polyethylene and biomass mixture

[0075]

[0076] Example 5

[0077] This embodiment provides a method for microwave catalytic dehydrogenation of polypropylene plastic, and the specific operation steps are as follows:

[0078] 1) crushing the collected polypropylene plastic and mixing it with the nickel-iron bimetallic nanocatalyst in a mass ratio of 3:1;

[0079] Wherein, the nickel-iron bimetallic nanocatalyst used in step 1 is prepared according to the following method:

[0080] Nickel acetate and ferric nitrate were mixed in a mass ratio of 1:5, and then deionized water was added and stirred into a uniform gel. The total mass ratio of deionized water to the two metal salts was 1:7. The gel catalyst precursor was calcined at 550°C in an air atmosphere for 2 hours to obtain a nickel-iron bimetallic nanocatalyst.

[0081] 2) If Figure 1As shown, 8 g of the uniformly mixed reaction material in step 1 was taken and placed in a microwave reactor. Before microwave irradiation, nitrogen was purged for 10 min (100 ml / min) to exclude oxygen. Then, a catalytic dehydrogenation reaction was carried out at a microwave power of 700 W for 10 min. The reaction product was condensed and separated to obtain gas and oil. Solid residue remained in the reactor. The product composition was then quantitatively and qualitatively analyzed. The results are shown in Table 5.

[0082] Table 5 Distribution of products of microwave catalytic dehydrogenation of polypropylene

[0083]

[0084] Example 6

[0085] This embodiment provides a method for microwave catalytic dehydrogenation of polypropylene plastic, and the specific operation steps are as follows:

[0086] 1) crushing the collected polypropylene plastic and mixing it with the nickel metal nanocatalyst in a mass ratio of 1:1;

[0087] Wherein, the nickel metal nanocatalyst used in step 1 is prepared according to the following method:

[0088] Nickel acetate and nickel nitrate were mixed in a mass ratio of 4:1, and then deionized water was added and stirred into a uniform gel, and the total mass ratio of deionized water to the two metal salts was 1:3. The gel catalyst precursor was calcined at 550°C in an inert atmosphere for 2h to obtain a nickel metal nanocatalyst.

[0089] 2) If Figure 1 As shown, 16 g of the uniformly mixed reaction material in step 1 was taken and placed in a microwave reactor. Before microwave irradiation, nitrogen was purged for 10 min (100 ml / min) to exclude oxygen. Then, a catalytic dehydrogenation reaction was carried out at a microwave power of 1000 W for 10 min. The reaction product was condensed and separated to obtain gas and oil. Solid residue remained in the reactor. The product composition was then quantitatively and qualitatively analyzed. The results are shown in Table 6.

[0090] Table 6 Distribution of products from microwave catalytic dehydrogenation of polypropylene

[0091]

[0092]

[0093] Example 7

[0094] This embodiment provides a method for microwave catalytic dehydrogenation of polyolefin mixed plastics, and the specific operation steps are as follows:

[0095] 1) crushing the collected waste polyethylene plastics, waste polypropylene plastics and waste polystyrene plastics, mixing them in a mass ratio of 3:3:1, and then mixing them with nickel-cobalt-iron trimetallic nanocatalysts in a mass ratio of 2:1;

[0096] Wherein, the nickel-cobalt-iron trimetallic nanocatalyst used in step 1 is prepared according to the following method:

[0097] Nickel acetate, cobalt acetate and ferric citrate were mixed in a mass ratio of 5:2:2, and then deionized water was added and stirred into a uniform gel, the total mass ratio of deionized water to trimetallic salt was 1:8, and the gel catalyst precursor was calcined at 600° C. in an inert atmosphere for 4 h to obtain a nickel-cobalt-iron trimetallic nanocatalyst;

[0098] 2) If Figure 1 As shown, 15 g of the uniformly mixed reaction material in step 1 was taken and placed in a microwave reactor. Before microwave irradiation, nitrogen was purged for 10 min (100 ml / min) to exclude oxygen. Then, a catalytic dehydrogenation reaction was carried out at a microwave power of 1200 W for 10 min. The reaction product was condensed and separated to obtain gas and oil. Solid residue remained in the reactor. The product composition was then quantitatively and qualitatively analyzed. The results are shown in Table 7.

[0099] Table 7 Distribution of products from microwave catalytic dehydrogenation of polyolefin mixed plastics

[0100]

[0101] Example 8

[0102] This embodiment provides a microwave catalytic dehydrogenation method for polyolefin mixed plastics, and the specific operation steps are as follows:

[0103] 1) crushing the collected polyethylene plastic, polypropylene plastic and polystyrene plastic, mixing them in a mass ratio of 9:2:1, and then mixing them with a nickel-iron bimetallic nanocatalyst in a mass ratio of 9:1;

[0104] Wherein, the nickel-iron bimetallic nanocatalyst used in step 1 is prepared according to the following method:

[0105] Nickel acetylacetonate and ferric citrate were mixed in a mass ratio of 1:1, and then deionized water was added and stirred into a uniform gel. The total mass ratio of deionized water to the two metal salts was 1:3. The gel catalyst precursor was calcined at 400°C in an air atmosphere for 2 hours to obtain a nickel-iron bimetallic nanocatalyst.

[0106] 2) If Figure 1As shown, 10 g of the reaction material mixed evenly in step 1 was taken and placed in a microwave reactor. Before microwave irradiation, nitrogen was purged for 10 min (100 ml / min) to exclude oxygen. Then, a catalytic dehydrogenation reaction was carried out at a microwave power of 1200 W for 10 min. The reaction product was condensed and separated to obtain gas and oil. Solid residue remained in the reactor. The product composition was then quantitatively and qualitatively analyzed. The results are shown in Table 8.

[0107] Table 8 Distribution of products from microwave catalytic dehydrogenation of polyolefin mixed plastics

[0108]

[0109]

[0110] Example 9

[0111] This embodiment provides a microwave catalytic dehydrogenation method for a mixed polyolefin and fiber mixture, and the specific operation steps are as follows:

[0112] 1) Mixing the crushed polyethylene plastic, polypropylene plastic, polystyrene plastic and polyurethane in a mass ratio of 3:10:1:1, and then mixing with the iron metal nanocatalyst in a mass ratio of 1:2;

[0113] Wherein, the iron metal nanocatalyst used in step 1 is prepared according to the following method:

[0114] Ferric citrate and ferric acetylacetonate were mixed in a mass ratio of 6:1, and then deionized water was added and stirred into a uniform gel, the total mass ratio of deionized water to the two metal salts was 1:7, and the gel catalyst precursor was calcined at 550° C. in an inert atmosphere for 3 h to obtain an iron metal nanocatalyst;

[0115] 2) If Figure 1 As shown, 15 g of the uniformly mixed reaction material in step 1 was taken and placed in a microwave reactor. Before microwave irradiation, nitrogen was purged for 10 min (100 ml / min) to exclude oxygen. Then, a catalytic dehydrogenation reaction was carried out at a microwave power of 1000 W for 10 min. The reaction product was condensed and separated to obtain gas and oil. Solid residue remained in the reactor. The product composition was then quantitatively and qualitatively analyzed. The results are shown in Table 9.

[0116] Table 9 Distribution of products from microwave catalytic dehydrogenation of mixed polyolefin and fiber mixture

[0117]

[0118] Example 10

[0119] This embodiment provides a method for dehydrogenating mixed plastics in a landfill by microwave catalysis, and the specific operation steps are as follows:

[0120] 1) crushing the plastic mixture recovered from the garbage dump without any treatment, and then mixing the mixture with the nickel-cobalt-iron trimetallic nanocatalyst in a mass ratio of 1:2;

[0121] Wherein, the nickel-cobalt-iron trimetallic nanocatalyst used in step 1 is prepared according to the following method:

[0122] Nickel chloride, cobalt carbonyl and ferric citrate are mixed in a mass ratio of 1:5:7, and then deionized water is added and stirred into a uniform gel. The total mass ratio of deionized water to trimetallic salt is 1:3. The gel catalyst precursor is calcined at 500°C in an inert atmosphere for 3 hours to obtain a nickel-cobalt-iron trimetallic nanocatalyst.

[0123] 2) If Figure 1 As shown, 30 g of the uniformly mixed reaction material in step 1 was taken and placed in a microwave reactor. Before microwave irradiation, nitrogen was purged for 10 min (100 ml / min) to exclude oxygen. Then, a catalytic dehydrogenation reaction was carried out at a microwave power of 1200 W for 10 min. The reaction product was condensed and separated to obtain gas and oil. Solid residue remained in the reactor. The product composition was then quantitatively and qualitatively analyzed. The results are shown in Table 10.

[0124] Table 10 Distribution of products from microwave catalytic dehydrogenation of mixed plastics in landfills

[0125]

[0126]

[0127] Comparative Example 1

[0128] This comparative example provides a microwave catalytic dehydrogenation method for polyolefin mixed plastics, and the specific operating steps are as follows:

[0129] 1) crushing the collected polyethylene plastic, polypropylene plastic and polystyrene plastic, mixing them in a mass ratio of 9:2:1, and then mixing them with a nickel-iron bimetallic nanocatalyst in a mass ratio of 9:1;

[0130] Wherein, the nickel-iron bimetallic nanocatalyst used in step 1 is prepared according to the following method:

[0131] Nickel nitrate and ferric nitrate were mixed in a mass ratio of 1:1, and then deionized water was added and stirred into a uniform gel. The total mass ratio of deionized water to the two metal salts was 1:3. The gel catalyst precursor was calcined at 400°C in an air atmosphere for 2 hours to obtain a nickel-iron bimetallic nanocatalyst.

[0132] 2) If Figure 1As shown, 10 g of the reaction material mixed evenly in step 1 was taken and placed in a microwave reactor. Before microwave irradiation, nitrogen was purged for 10 min (100 ml / min) to exclude oxygen. Then, a catalytic dehydrogenation reaction was carried out at a microwave power of 1200 W for 10 min. The reaction products were condensed and separated to obtain gas and oil. Solid residue remained in the reactor. The product composition was then quantitatively and qualitatively analyzed. The results are shown in Table 11.

[0133] Table 11 Distribution of products from microwave catalytic dehydrogenation of polyolefin mixed plastics

[0134]

[0135] Comparative Example 2

[0136] This comparative example provides a microwave catalytic dehydrogenation method for polyolefin mixed plastics, and the specific operating steps are as follows:

[0137] 1) crushing the collected polyethylene plastic, polypropylene plastic and polystyrene plastic, mixing them in a mass ratio of 9:2:1, and then mixing them with a nickel-iron bimetallic nanocatalyst in a mass ratio of 9:1;

[0138] Wherein, the nickel-iron bimetallic nanocatalyst used in step 1 is prepared according to the following method:

[0139] Nickel nitrate, ferric nitrate and activated carbon were mixed in a mass ratio of 9:9:1, and then deionized water was added and stirred into a uniform gel. The total mass ratio of deionized water and the two metal salts was 1:3. The gel catalyst precursor was calcined at 400°C in an inert atmosphere for 2h to obtain a nickel-iron bimetallic nanocatalyst.

[0140] 2) If Figure 1 As shown, 10 g of the reaction material mixed evenly in step 1 was taken and placed in a microwave reactor. Before microwave irradiation, nitrogen was purged for 10 min (100 ml / min) to exclude oxygen. Then, a catalytic dehydrogenation reaction was carried out at a microwave power of 1200 W for 10 min. The reaction products were condensed and separated to obtain gas and oil. Solid residue remained in the reactor. The product composition was then quantitatively and qualitatively analyzed. The results are shown in Table 12.

[0141] Table 12 Distribution of products from microwave catalytic dehydrogenation of polyolefin mixed plastics

[0142]

[0143]

[0144] Test Example 1

[0145] The catalysts prepared in Example 1, Example 2, Example 5 and Example 6 were characterized by XRD. Figure 2 , from which it can be seen that the catalysts obtained were successfully prepared and showed good crystallinity.

[0146] Test Example 2

[0147] The catalysts prepared in Example 2, Example 6 and Example 7 were characterized by SEM or TEM. Figure 3 It can be seen that the particle size of most catalyst particles is much smaller than the scale length (<<500nm), indicating that the nanocatalyst was successfully prepared; at the same time, it can be seen that the nanocatalyst particles are isolated by a layer of carbon, forming a good dispersion effect, which can effectively avoid aggregation and sintering between the catalysts and is beneficial to improving their catalytic activity.

[0148] Test Example 3

[0149] The carbon residue obtained by microwave catalytic dehydrogenation of organic solid waste in Example 1, Example 4, and Example 10 was characterized by SEM or TEM, see Figure 4 , from which we can see that the residual carbon is filamentous carbon, and further from TEM we can see that the filamentous carbon is carbon nanotubes.

[0150] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A method for preparing a metal nanocatalyst, characterized in that: The steps include: calcining the transition metal salt at 300-1000°C for 1-6h to obtain a metal nanocatalyst; Wherein, the transition metal salt contains at least one transition metal salt containing carbon elements.

2. The preparation method according to claim 1, characterized in that: The transition metal salt is selected from one or more of nickel salts, cobalt salts and iron salts; The nickel salt is selected from one or more of nickel acetate, nickel nitrate, nickel chloride and nickel acetylacetonate; The cobalt salt is selected from one or more of cobalt acetate, cobalt nitrate, cobalt carbonyl, cobalt chloride and cobalt acetylacetonate; The iron salt is selected from one or more of ferric citrate, ferric nitrate, ferric acetylacetonate and ferric acetate.

3. The preparation method according to claim 1, characterized in that: When the transition metal salt includes a transition metal salt containing a carbon element and a transition metal salt not containing a carbon element, the mass ratio of the transition metal salt containing a carbon element to the transition metal salt not containing a carbon element is 0.1-20:

1.

4. The preparation method according to claim 1, characterized in that: The calcining atmosphere is selected from one of an air atmosphere, an inert atmosphere and a H2 / inert gas mixed atmosphere.

5. A metal nanocatalyst, characterized in that: The preparation is obtained by the preparation method according to any one of claims 1 to 4.

6. The metal nanocatalyst according to claim 5, characterized in that The particle size of the metal nanocatalyst is 1-500nm.

7. Use of the metal nanocatalyst as claimed in claim 5 or 6 in catalytic decomposition of organic solid waste.

8. The use according to claim 7, characterized in that: The application is specifically: Under an inert atmosphere, the organic solid waste and the metal nanocatalyst are placed in a microwave reactor, treated at a microwave power of 300-2000 W for 1-20 minutes, and the reaction products are collected and separated.

9. The use according to claim 8, characterized in that: The organic solid waste is selected from one or more of crop straw, forestry waste, waste plastic, cellulose, hemicellulose, lignin, lignocellulose, monosaccharide, amino acid and polysaccharide.

10. The use according to claim 8, characterized in that: The mixing mass ratio of the metal nanocatalyst to the organic solid waste is 0.05-30:1.